Kelyflata gen. nov. adds to Selizini flatids in Madagascar (Hemiptera: Fulgoromorpha: Flatidae) - Świerczewski, Dariusz; Stroiński, Adam (Zootaxa, 2019)
A new genus of flatid planthoppers (Hemiptera: Fulgoromorpha: Flatidae), Kelyflata gen. nov., is described for Kelyflata capensis sp. nov. (type species) and Kelyflata ilakakae sp. nov. from the island of Madagascar. Habitus, male external and internal genital structures of the new species are illustrated. Kelyflata is probably endemic to Madagascar where it is known to date, only from a southern part of the island.